Il profilo economico, patrimoniale e finanziario del sistema universitario italiano: Analisi dei bilanci degli atenei statali nel triennio 2018-2020 - Coran, Giovanni (Milan Higher Education Observatory-MHEO, 2023)
The essay reports the results of a research aimed at identifying and measuring the most relevant accounting ratios for assessing the degree of economic, equity and financial balance of the Italian state university system. For the first time, the financial statements of all 67 state universities were collected, aggregated, reclassified, and analysed over the three-year period 2018-2020. This analysis gives a very detailed overview of the system, showing its strengths and weaknesses, problems, and paradoxes. In addition, the work proposes an appropriate system of indicators to improve awareness of the processes of allocation and management of financial resources, both at the level of every single university, and of the university system as a whole.